MISKONSEPSI SISWA MATERI OPERASI HITUNG PECAHAN CAMPURAN KELAS V SEKOLAH DASAR DITINJAU DARI PEMAHAMAN KONSEP - Indri Nurlaili Putri; Dian Kusmaharti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics is something that is not far from formulas, of course several concepts will arise in solving problems in mathematics. If in and several concepts This research aims to describe students' misconceptions about the material on operations to calculate mixed fractions based on concept understanding in the criteria for high mathematical understanding, the criteria for moderate mathematical understanding, and the criteria for low mathematical understanding. The subjects of this research were fifth grade students at SDN Ngagel Rejo I/396 Surabaya. One subject has high mathematical understanding criteria, one subject has moderate mathematical understanding criteria, and one subject has low mathematical understanding criteria. The form of this research is qualitative. The data collection technique used was written tests and interviews, while the research instrument used was a misconception test which consisted of description/essay questions and interview guidelines. The data analysis technique for this research is through data reduction, data presentation, and drawing conclusions. This research was conducted on class V students of SDN Ngagel Rejo I/396 Surabaya. The results of this research show that several students stated that they still had difficulty operating mixed fractions into improper fractions and vice versa, they encountered several students who had difficulty working with fractions with different denominators, were unable to simplify fractions, and had difficulty understanding word problems.